1990
DOI: 10.1016/0952-3278(90)90178-n
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin deficiency

Abstract: Healthy cells from virtually all tissues synthesize a variety of prostaglandins, autacoids which can significantly alter cellular functions. An absolute or relative deficiency of prostaglandins has now been demonstrated in many diseases or clinical conditions. These include 'natural' disorders such as peptic ulcer disease and diabetes mellitus. These also include 'acquired' or iatrogenic conditions such as cyclosporine nephrotoxicity and the gastropathy induced by nonsteroidal anti-inflammatory drugs. We belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Prostaglandin G1 is a small molecular pro-inflammatory mediator derived from arachidonic acid that plays roles in, inflammation, pain modulation, allergies, and bone formation (Doucette and Walter 2017). An absolute or relative deficiency of prostaglandins has been observed in many diseases (Moran and Nicholson 1990). The levels of prostaglandin G1in the plasma of HUA rats was significantly lower than those in the C, L, and H groups (Figure 2A).…”
Section: Astragalus Membranaceus Ultrafine Powdermentioning
confidence: 85%
“…Prostaglandin G1 is a small molecular pro-inflammatory mediator derived from arachidonic acid that plays roles in, inflammation, pain modulation, allergies, and bone formation (Doucette and Walter 2017). An absolute or relative deficiency of prostaglandins has been observed in many diseases (Moran and Nicholson 1990). The levels of prostaglandin G1in the plasma of HUA rats was significantly lower than those in the C, L, and H groups (Figure 2A).…”
Section: Astragalus Membranaceus Ultrafine Powdermentioning
confidence: 85%
“…Our study confirmed and extended this notion by showing that the resolution of allergic inflammation was observed only when chronic OVA challenges were delivered at mucosal surface (airway) but not when administered into serosal peritoneal cavity, indicating that the site where OVA is given is fundamental for the resolution of allergic inflammation induced by long-term allergen challenges. The major pathways of anti-inflammatory mechanisms involve are as follows: (1) production of anti-inflammatory substances such as suppressive cytokines (IL-10, TGF-b; 45,46 ), bioactive lipids (lipoxin 47 and prostaglandins 48 ), and endogenous mediators (glucocorticoids 49 and acetylcholine 50 ); (2) Induction of regulatory cells (e.g., suppressor lymphocytes such as Treg, Tr1, Th3, regulatory B, and CD8 þ T cells, suppressor macrophages, and mesenchymal cells [51][52][53][54] ; and (3) apoptosis of infiltrating inflammatory cells including effector T cells. 35,55,56 All these pathways are highly regulated and implicated in resolution of inflammatory processes and re-establishment of tissue homeostasis and failures in those immunoregulatory mechanisms can result in progression and/or persistence of a range of inflammatory diseases including asthma.…”
Section: Discussionmentioning
confidence: 99%